The safe surgical margin in Ewing's sarcoma. (May 2022) - Nogaro, Marie-Caroline; Mifsud, Max; McCarthy, Catherine; Orosz, Zsolt; Pratap, Sarah; Craig, Richard; Cosker, Thomas DA.; Gibbons, CLMH; Theologis, Tim
Abstract: Introduction: There is recent evidence advocating the use of post-chemotherapy MRI for safe resection of primary bone sarcoma in providing a clear margin of disease. This paper challenges this view by providing evidence obtained from comparing surgical resection margin measurements calculated off the pre- and post-chemotherapy MRIs to the post-operative histological analysis. Method: A retrospective patho-radiological analysis of 10 patients treated for long bone Ewing's sarcoma. The pre- and post-chemotherapy MRI radiological measurements were correlated with the post-operative gross and microscopic histological specimens with the principle aim of determining which represented the accurate histological extent of disease and therefore which image set should be used in determining the surgical resection margins. Results: In the 10 cases there was a discrepanc y in the extent of pathological disease on comparative histological and radiological assessment. The mean age at presentation was 19.5years [4–45 years], with a female bias (n = 7/10). The lower limbs were more commonly involved than the upper limb (femur n = 2/10, tibia n = 3/10, fibula n = 2/10, humerus n = 2/10, ulna n = 1/10). There was no correlation between the percentage reduction in measured volume/length of pathological bone on sequential MRI and the percentage necrosis on histology. The average discrepancy between the length of pathological bone on histology and on MRI was 2.7 cm. Using the baseline pre-chemotherapy MRI to plan the surgical resection margins, 7/10 patients had their surgical resection margins through radiologically clear but pathologically abnormal bone (without histological evidence of residual tumour). Had the post-chemotherapy MRI been used a further 3 patients would have had their tumour resected through pathologically abnormal bone. No patients had or would have had tumour resected through residual tumour. Conclusions: The use of the post-chemotherapy MRI for planning surgical resection margins increases the risk of resecting through histologically abnormal bone that may have been previously contaminated by tumour, without significant benefit of preserving sufficient bone to facilitate joint or physeal sparing surgery. The evidence from this study supports current guidelines recommending the use of pre-chemotherapy MRI to plan safe surgical resection margins in Ewing's sarcoma. Highlights: Pre-chemotherapy MRI should be used when planning resection margins for Ewing's sarcoma. Using post-chemotherapy increases the risk of resecting through histologically abnormal bone. Survey of current UK practices (BOOS) supports use of pre-chemotherapy MRI for planning.